SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (Literatur Review) - Winda Aulia Rahman; Yasinda Apriani; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2023)
The Occupational Safety and Health Management System is part of the overall management system which includes the organizational structure, planning, responsibilities, implementation of procedures, processes and resources required for the development, implementation, achievement, review and maintenance of policies.